Effectiveness of cognitive play in developing the self-confidence of the mentally handicapped who are able to learn during COVID-19 pandemic - Hamza, Reham; Bioumy, Awatef (Technium Social Sciences Journal, 2021)
The study aimed to identify the effectiveness of cognitive play in developing the self-confidence of the mentally handicapped who are able to learn, and verify the effectiveness of the program, and the study sample consisted of (20) children with intellectual disabilities who are able to learn who are inIntellectual Education. The study sample was divided into two groups.The experimental group(10)children, and the control group (10) children, of the mentally handicapped children who are able to learn, their ages ranged between (9-12), and their IQs ranged between (50-70), and the researcher used in the study the quasi-experimental approach The researcher applied the following tools to the study sample: the Stanford Binet Scale (5thimage), citation and preparation. The self-confidence scale, andthe existing training program.On the cognitive play used in the current research, the researcher numbers, and the results of the study revealed.There are statistically significant differences between the average scores of children in the post-measurement on the scale of self-confidence.There are statistically significant differences between the mean scores of the control group and the experimental group on the self-confidence scale in the post-measurement in favor of the experimental group .Predicting the effectiveness of the training program based on cognitive play in developing self-confidence in mentally handicapped children who are able to learnduring COVID-19 pandemic.